The Existence Of The Village Secretary From Civil Servants In The Administration Of The Village Government : (The Study in Sub-district of North Luwuk in Banggai District) - Nur, Nirwan Moh.; Risno Mina (STAI Miftahul Ula Nganjuk, 2024)
The existence of village secretaries from civil servants is expected to make the village government management more effective, especially in the service to the community. However, as mentioned above, expectations in other perspectives need to be tested in the field. The village perspective as a community unit which is having an original autonomy based on its origin and custom, the presence of village secretaries from civil servant is certainly subjects to the norms of personnel in carrying out their duties and responsibilities. In the northern Banggai in Luwuk district, the village secretaries from civil servants are very helpful and have the ability to administer the public service administration and governance. But in the preparation of the annual work program and the village budgets, every year the village secretary is not optimal in carrying out their duties. The labor relation and the village secretary relationship with other tools in other villages in assisting the village head in order to strengthen the village autonomy and in order to improve the public services and in the development of village has proceeded well.